Reduced activation and expression of ERK1/2 MAP kinase in the post‐mortem brain of depressed suicide subjects - Dwivedi, Y.; Rizavi, H. S.; Roberts, R. C.; Conley, R. C.; Tamminga, C. A.; Pandey, G. N. (Journal of neurochemistry, 2001)
The extracellular regulated kinases (ERK) 1 and ERK2 are members of mitogen‐activated protein (MAP) kinase family that play an important role in transducing extracellular signals to the nucleus and have been implicated in a broad spectrum of biological responses. To test the hypothesis that MAP kinases may be involved in depression, we examined the activation of p44/42 MAP kinase and expression of ERK1 and ERK2 in the post‐mortem brain tissue obtained from non‐psychiatric control subjects (n = 11) and age‐ and the post‐mortem interval‐matched depressed suicide subjects (n = 11). We observed that p44/42 MAP kinase activity was significantly decreased in the prefrontal cortical areas (Brodmann's areas 8, 9 and 10) and the hippocampus of depressed suicide subjects without any change in the cerebellum. This decrease was associated with a decrease in mRNA and protein levels of ERK1 and ERK2. In addition, the expression of MAP kinase phosphatase (MKP)2, a ‘dual function’ ERK1/2 phosphatase, was increased in the prefrontal cortex and hippocampus. These studies suggest that p44/42 MAP kinases are less activated in the post‐mortem brain of depressed suicide subjects and this may be because of reduced expression of ERK1/2 and increased expression of MKP2. Given the role of MAP kinases in various physiological functions and gene expression, alterations in p44/42 MAP kinase activation and expression of ERK1/2 may contribute significantly to the pathophysiology of depressive disorders.